THE INTERPRETATION OF RELIGIOUS UNDERSTANDING OF HEARING AND SPEECH-IMPAIRED CHILDREN - Nufitriani Kartika Dewi; Syifa Fauziah; Himmah Taulany (Universitas Muhammadiyah Ponorogo, 2019)
This study aimed to find out the interpretation of the religious understanding of hearing and speech-impaired children whether it is in accordance with thinking theory in religious psychology according to Piaget, Salkind, Hurlock and Zakiah Daradjat. This qualitative research used interviews to obtain the interpretation of children's religious understanding. The eight aspects that are explored are religion, God, prayer, merit and sin, angels and demons, heaven and hell, death and doomsday. The results of this study indicated that 7 and 8 year old children with hearing impairments interpreted the eight aspects of the religion with religious symbols, and with something that is made real to them. This is in accordance with the theories of Piaget, Salkind, Hurlock, and Zakiah Daradjat; Children who are totally deaf could interpret religion, hell and death in more detail than children who still have very good hearing. From this study, it was also obtained the factors that influence and the constraints, namely age and its hearing impairement, were the reason for parents and teachers not to provide in-depth and precise information about religion due to limitations in communication. Therefore, the researcher provide advice in the form of a good two-way communication approach between parents and children and visual media become one of the good and appropriate communication media to help communicate with hearing and speech-impaired children.